Assessment of shelf stability of noodles fortified with button mushroom and chickpea starch - Shams, Rafeeya; Singh, Jagmohan; Dar, Aamir Hussain (Journal of Postharvest Technology, 2022)
Instant noodles were prepared by supplementing wheat flour with mushroom and chickpea starch at different concentrations (100:0:0,  90:5:5, 80:10:10, 70:15:15, 60:20:20:: wheat flour: mushroom powder: chickpea starch). In present study, the further assessment was  undertaken to assess the effect of value addition of mushroom powder and chickpea starch on the nutritional profile, cooking quality,  bioactive properties and shelf stability of fortified noodles. The addition of mushroom powder resulted in increase in crude protein, fibre  content, yellowness (b*) and redness (a*) and decrease in carbohydrate, lightness (L*) and cooking time. The developed noodles also  showed increase in antioxidant activity, water absorption capacity and cooking loss. Sensory scores showed that the addition of 10%  mushroom powder resulted in better quality noodles with highest overall acceptability. However, with the advancement of storage there was  decrease in the nutritional profile but still can be beneficial for human health.
Keywords: Fortified noodle; fortification; shelf life; nutritional quality